2017
DOI: 10.1097/igc.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Stromal Sarcoma of the Uterus: Magnetic Resonance Imaging Findings Including Apparent Diffusion Coefficient Value and Its Correlation With Ki-67 Expression

Abstract: Patients with ESS showed some characteristics on conventional MRI and DWI, and there was an inverse correlation between the ADC value and Ki-67 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…International Publisher diffusion-weighted imaging (DWI) can reflect tumor cellularity. In recent years, ADC values were reported to be associated with Ki-67 expression in various tumors, such as breast cancer [8,9], endometrial stromal sarcoma of the uterus [10], endometrial carcinoma [11], and lung cancer [12]. However, ADC values are calculated using a mono-exponential model that is affected not only with the molecular movements of water but also by capillary microcirculation [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…International Publisher diffusion-weighted imaging (DWI) can reflect tumor cellularity. In recent years, ADC values were reported to be associated with Ki-67 expression in various tumors, such as breast cancer [8,9], endometrial stromal sarcoma of the uterus [10], endometrial carcinoma [11], and lung cancer [12]. However, ADC values are calculated using a mono-exponential model that is affected not only with the molecular movements of water but also by capillary microcirculation [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…Compared to leiomyosarcoma, less is known about the added value of DWI and ADC values in differentiation of LGESS from leiomyoma. Li et al reported that 12 of 13 LGESS cases showed high SI relative to uterine endometrium and skeletal muscle, except one case with iso SI 18 . Similar to their results, all LGESS cases in our study showed iso/high SI to sciatic nerve on DWI.…”
Section: Discussionmentioning
confidence: 99%
“…They were aware that patients had been diagnosed histologically as having either LGESS or rare leiomyoma variants, but they were blinded to all other clinical information. The following qualitative features were evaluated: on T2WI, (1) main site of the tumor (intramural, submucosal, or subserosal), (2) nodular and/or irregular border 15 , (3) extrauterine involvement, (4) worm-like nodular extension 15 , (5) intra-tumoral low SI bands 16 , (6) low SI rim surrounding intra-myometrial tumor 17 , (7) speckled appearance (reported to be characteristic of leiomyoma) 9 , 20 , (8) cystic and/or necrotic change 18 , (9) higher SI than outer myometrium; on T1WI images, (10) tumoral hemorrhage (intra-tumoral high SI), with worm-like nodular extension on T2WI defined as detached nodules from the primary tumor 15 , with speckled appearance defined as diffusely scattered high SI within the tumor on T2WI 20 . When DWI and CE-T1WI were available, the following features were assessed: (11) SI relative to sciatic nerve roots (iso or high vs low) on DWI and (12) heterogeneous tumor enhancement on CE-T1WI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations